Virtual Reality Exposure and Imaginal Exposure in the Treatment of Fear of Flying: A Pilot Study. (July 2013) - Rus-Calafell, Mar; Gutiérrez-Maldonado, José; Botella, Cristina; Baños, Rosa M.
Fear of flying (FF) is an impairing psychological disorder that is extremely common in developed countries. The most effective treatment for this particular type of phobia is exposure therapy. However, there are few studies comparing imaginal exposure (IE) and virtual reality (VR) exposure for the treatment of FF. The present study compared the effectiveness of these two approaches using two manualized interventions based on the exposure technique. Patients with FF ( N = 15) were randomly assigned to either VR ( n = 7) or IE therapy ( n = 8), consisting of a total of eight sessions: two assessment sessions (pre-treatment and after the real flight) and six exposure therapy sessions, which were conducted twice a week. During each exposure session, subjective perceived anxiety was measured every 5 min. Participants were also asked to sit through a real flight immediately after the treatment. The results showed no differences between the two treatments in relation to reduced clinical symptomatology associated with the FF, although participants in the VR group experienced less anxiety during the real flight after treatment. Furthermore, at 6-month follow-up, danger expectations and flight anxiety continued to decrease in participants who had received the VR exposure therapy, and four of these seven participants took at least one more flight.